The Cortical Motor System in the Domestic Pig: Origin and Termination of the Corticospinal Tract and Cortico-Brainstem Projections - del Cerro, Patricia; Rodríguez-De-Lope, Ángel; Collazos-Castro, Jorge E. (Frontiers in Neuroanatomy, 2021)
The anatomy of the cortical motor system and its relationship to motor repertoire in artiodactyls is for the most part unknown. We studied the origin and termination of the corticospinal tract (CST) and cortico-brainstem projections in domestic pigs. Pyramidal neurons were retrogradely labeled by injecting aminostilbamidine in the spinal segment C1. After identifying the dual origin of the porcine CST in the primary motor cortex (M1) and premotor cortex (PM), the axons descending from those regions to the spinal cord and brainstem were anterogradely labeled by unilateral injections of dextran alexa-594 in M1 and dextran alexa-488 in PM. Numerous corticospinal projections from M1 and PM were detected up to T6 spinal segment and showed a similar pattern of decussation and distribution in the white matter funiculi and the grey matter laminae. They terminated mostly on dendrites of the lateral intermediate laminae and the internal basilar nucleus, and some innervated the ventromedial laminae, but were essentially absent in lateral laminae IX. Corticofugal axons terminated predominantly ipsilaterally in the midbrain and bilaterally in the medulla oblongata. Most corticorubral projections arose from M1, whereas the mesencephalic reticular formation, superior colliculus, lateral reticular nucleus, gigantocellular reticular nucleus, and raphe received abundant axonal contacts from both M1 and PM. Our data suggest that the porcine cortical motor system has some common features with that of primates and humans and may control posture and movement through parallel motor descending pathways. However, less cortical regions project to the spinal cord in pigs, and the CST neither seems to reach the lumbar enlargement nor to have a significant direct innervation of cervical, foreleg motoneurons.